Planificación urbana y descentralización político-administrativa en Venezuela (1984-1994) - Rodríguez, Juan Carlos (Revista EURE - Revista de Estudios Urbano Regionales, 1995)
This work is about urban planning decentralization from a perspective that favours politic and administrative decentralization. Urban planning decentralization is considered within the framework of the venezuelan decentralization iniciatives in 1984 when the Comission for the Constitutional Reform (COPRE) was created. The work tries to conceptualize urban planning so as to contribute to interpretation of the decentralization propositions originated in this filed. It also describes and analyzes the current system of urban affairs in Venezuela, evidencing the high degree of centralization that still exists. Finally, two projects for the decentralization of urban planning in Venezuela are presented and analyzed and the perspectives of this process are sketched. Í 